Suspension of the employment contract: legal nature and perspectives of law enforcement - M. Vishnjakova (Правоприменение)
The subject of the paper is legal nature of suspension of the employment contract.The main aim of the paper is to confirm or disprove the hypothesis that it would be reasonable to provide for the possibility of suspension of the employment contract.The methodology of the study includes general scientific methods (analysis, synthesis, description) as well as particular academic legal methods (formal-legal method, interpretation of legal acts). The main results and scope of their application. Changes in industrialization and the global economic crisis inevitably lead to the fact that the standard schemes of relations between the employee and the employer do not meet the requirements of modern times. It needs to revise the structures of regulation of labour relations in Russian labor law. The suspension of an employment contract must be temporary and must continue until the circumstances giving rise to the suspension have been eliminated. The usage suspension of the employment contract entails the need for direct determination of the following guarantees for employees for the entire period: preservation of the employee's place of work (position); prohibition of dismissal of an employee on the initiative of the employer; inclusion of suspension period in the length of seniority for annual basic paid leave; preservation of the employee’s right to get a job with another employer on a part-time basis. The usage of suspension of the employment contract will allow to regulate new forms of employment activity: temporary redeployment of the employee to another employer and secondment into the labor law.Conclusions. It would be reasonable to provide for the possibility of suspension of the employment contract.